2010
DOI: 10.1007/s12032-010-9554-8
|View full text |Cite
|
Sign up to set email alerts
|

Significance of estrogen receptor 1 (ESR-1) gene imbalances in colon and hepatocellular carcinomas based on tissue microarrays analysis

Abstract: Estrogen receptor alpha-encoded by ESR1 gene-overexpression correlates with prognosis and response to specific chemotherapy in breast adenocarcinoma cases. Mechanisms of ESR-1 deregulation in carcinomas remain under investigation. To analyze ESR1 in carcinomas of different histogenesis. Using tissue microarray technology, 172 primary carcinomas including breast ductal adenocarcinomas (n=60), hepatocellular carcinomas (n=52), and colon adenocarcinomas (n=60) were cored and re-embedded in three paraffin blocks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…In contrast, wildtype ER-␤ was expressed more often in HCV patients than in HBV patients (95.7% vs. 44.4%; p < 0.05). Within Western population, 33-46% of HCC samples showed overexpression of ER (Tsiambas et al, 2011;Garcia-Leiva et al, 2006;Moon et al, 2004). In summary, aberrant ER, both in Asian (Sheng et al, 2014) and Western (Villa et al, 1995) population have been described and shown to have an impact in patients prognosis.…”
Section: Hormone Receptorsmentioning
confidence: 95%
“…In contrast, wildtype ER-␤ was expressed more often in HCV patients than in HBV patients (95.7% vs. 44.4%; p < 0.05). Within Western population, 33-46% of HCC samples showed overexpression of ER (Tsiambas et al, 2011;Garcia-Leiva et al, 2006;Moon et al, 2004). In summary, aberrant ER, both in Asian (Sheng et al, 2014) and Western (Villa et al, 1995) population have been described and shown to have an impact in patients prognosis.…”
Section: Hormone Receptorsmentioning
confidence: 95%
“…For example, using a cut off of > 2.0 instead of ≥ 2.0 for amplification calling, or a ratio 2.2 instead of 1.8, can change the amplification frequency by almost 50% [22,49,50] . In a recent study done with use of next-generation sequencing (NGS), the threshold of ≥ 6 average copies [as recommended for ERBB2 (HER2) testing [46] ] in tissue samples with tumor purity of > 20% resulted in only 0.8% ESR1 amplification across samples [51] .…”
Section: Definitions and Referencesmentioning
confidence: 99%
“…However, regardless of the prevalence of gene amplification across a tumor type, the increase in copy number for a given gene is a well-known mechanism for increasing its expression [16,17,44,92,93] ; accordingly, gene amplification is assumed to be a marker for a tumor's addiction to the expression of the amplified gene [18,19] . Several reports, including those that use DNA-specific methods for ESR1 copy number determination, have documented a significant correlation between ESR1 gene amplification and ERα protein expression [24,25,28,50,67,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] ( Table 1).…”
Section: Gains For Expressionmentioning
confidence: 99%
See 2 more Smart Citations